A Novel Class of Dopamine D4 Receptor Ligands Bearing an Imidazoline Nucleus. (15th March 2016) - Mammoli, Valerio; Bonifazi, Alessandro; Dal Ben, Diego; Giannella, Mario; Giorgioni, Gianfabio; Piergentili, Alessandro; Pigini, Maria; Quaglia, Wilma; Thomas, Ajiroghene; Newman, Amy H.; Ferré, Sergi; Sanchez‐Soto, Marta; et al.
Abstract: Over the years, the 2‐substituted imidazoline nucleus has been demonstrated to be a bioversatile structural motif. In this study, novel imidazoline derivatives bearing a 3‐ and/or 4‐hydroxy‐ or methoxy‐substituted phenyl ring, linked by an ethylene bridge to position 2 of an N ‐benzyl‐ or N ‐phenethyl‐substituted imidazoline nucleus, were prepared and studied against D2 ‐like receptor subtypes. Binding studies highlighted that a set of N ‐phenethylimidazoline compounds are selective for D4 over D2 and D3 receptors. In functional assays, the 3‐methoxy‐substituted derivative, endowed with the highest D4 affinity value, and its 3‐hydroxy analogue behaved as partial agonists with low intrinsic efficacy and as competitive D4 antagonists when tested in the presence of the D2 ‐like receptor agonist quinpirole. Molecular docking analysis, performed using a homology model of the human D4 receptor developed using the X‐ray crystal structure of the antagonist‐bound human D3 receptor as a template, was in accordance with the binding results and provided useful information for the design of novel imidazoline D4 receptor ligands based on this new scaffold. Abstract : That's pretty dope(amine) : Focusing on dopamine D2 ‐like receptors, we identified novel imidazoline ligands based on a bioversatile scaffold. The most interesting compounds were selective for D4 over D2 and D3 receptors and behaved as competitive D4 antagonists. These results provide useful information for further optimization of this novel class of compounds.